Optimasi formula sampo ekstrak etanol daun delima (Punica granatum L.) dengan metode Simplex Lattice Design - Jannah, Syifaul; Hajrin, Wahida; Hanifa, Nisa Isneni (Sasambo Journal of Pharmacy, 2024)
Anti-dandruff shampoo on the market still uses zinc pyriton which has the side effect of causing hair loss. Pomegranate leaves have strong antifungal activity against dandruff-causing fungi. This research aims to determine the optimum formula and physical properties of pomegranate leaf shampoo preparations with variations of SLS and cocamide DEA. The ethanol extract of pomegranate leaves was extracted by soxhletation and carried out in a tube test. Eight shampoo formula designs were determined using the SLD method. The shampoo was tested for foam height, pH, and viscosity to obtain the optimum formula. The optimum shampoo preparation was tested for physical properties, including organoleptic tests, homogeneity, foam stability, foam height, pH, and viscosity. The results of the test for the physical properties of the optimum shampoo preparation were verified using the SPSS application with the one-sample t-test method. Pomegranate leaf ethanol extract positively contains alkaloids, flavonoids, tannins, and saponins. The optimization results obtained the optimum shampoo formula, namely a combination of SLS 5.5% and cocamide DEA 15.5%. Optimum formula shampoo has a black color, menthol odor, gel form, ingredients mixed homogeneously, foam stability 81.83%, foam height 9.30 ± 0.26 cm, pH 5.91 ± 0.45, and viscosity 1646.66 ± 220.23 cP.